Effect of Managerial Ownership, Return on Assets, and Company Size on Disclosure of Corporate Social Responsibility - Serli Marlina (PT. Publikasiku Academic Solution, 2022)
Background: This research is motivated by the gap between companies that are required to play an active role in the preservation and welfare of the environment around the company. Corporate Social Responsibility can be an advantage for various parties, including the government, companies, employees, and the surrounding community. Corporate Social Responsibility is an accounting concept that emphasizes corporate responsibility to the environment and society. Aim: Analyzing the effect of Managerial Ownership, Return On Assets, and Company Size on Corporate Social Responsibility Disclosures simultaneously or partially in textile and garment sub-sector companies listed on the Indonesia Stock Exchange (IDX) in 2016-2020. Method: The method used in this research is a descriptive method and verification method. The data analysis technique in this study used panel data regression analysis. Findings: Based on the results of the t-test (partial) show that Managerial Ownership, Return On Assets, and Company Size have a significant positive effect on the Disclosure of Corporate Social Responsibility. Based on the F (simultaneous) test, shows that Managerial Ownership, Return On Assets, and Company Size together have a significant effect on Corporate Social Responsibility Disclosure.